Throw Yo' Voice Out: Disability as a Desirable Practice in Hip-Hop Vocal Performance - Alex S. Porco (Disability Studies Quarterly, 2014)
Disabled bodies and disabling spaces— especially the recording studio— shape the sound iconicity of hip-hop vocal performances. The disabled voice is the audible sign by which hip-hop artists trouble cultural definitions of the self and other; exceptionalism and failure; the natural and techno-mediated; comedy and tragedy; and aesthetic play and seriousness. Hip-hop vocal performances also function as self-conscious acts of transvaluation that challenge the discursive dominance of ableism. A materialist approach to vocal performance resists reducing voice to a silent metaphor for race, oppositionality, or liberation; and it emphasizes, instead, the physiological and social processes that render hip-hop voices unique, particular, and audible. It emphasizes the agency hip-hop artists possess in seeking out disabled bodies and assuming disabled identities for aesthetic and political ends. Thus, the body is returned to the analysis of style.
Keywords: Hip-Hop; Voice; Performance; Poetics